Prevalensi Anosmia dan Komorbiditas Pasien Covid-19 Sedang - Berat di RSUP Dr M Djamil Padang Tahun 2020 - Irwan Triansyah; Dian Ayu; Revalna Anestaria (Jurnal Ilmiah Manusia Dan Kesehatan, 2022)
The current coronavirus disease (COVID-19) pandemic anosmia and dysgeusia have been described as important symptoms of the disease. Clinical syndromes arising from infection with the SARS-CoV-2 virus can be of various kinds. Research by the American Academy of Otolaryngology shows anosmia occurs in 73% of patients and shows that anosmia is one of the important symptoms that arise from COVID-19 and to identify COVID-19 patients. To find out the description of anosmia in moderate-to-severe COVID-19 patients at RSUP Dr. M. Djamil Padang in 2020. The scope of the research is in the field of Ear Nose Throat Science. The research was conducted in the medical records section of Dr. RSUP. M. Djamil Padang. This research was conducted from August to September 2021. The type of research was descriptive categorical. The population in this study were all patients diagnosed with moderate-to-severe COVID-19 at RSUP Dr. M. Djamil Padang in 2020 as many as 106 samples with the Consecutive sampling technique. Univariate data analysis is presented in the form of frequency distribution and data processing using computerized SPSS program version IBM 24.0. Almost the same between male and female sexes with moderate-severe COVID-19, the mean age of moderate-severe COVID-19 patients was 49.68 (SD ± 12.63) years, which was dominated by the 52-53 age group. years with a total of 8 people, hypertension comorbid factor, as many as 35 people (33%), Diabetes Mellitus as many as 16 (15%) people, and cardiovascular disorders 8 people and 57 patients (53.8%) moderate-severe COVID-19 at RSUP Dr M Djamil Padang in 2020 does not suffer from anosmia. Conclusion: Almost the same between the sexes of women and men who suffer from moderate-severe COVID-19. The mean age of patients suffering from moderate-to-severe COVID-19 was 49 years and a standard deviation of 12.63. The most common comorbid disease suffered by patients was hypertension, followed by diabetes mellitus and cardiovascular disorders and complaints of anosmia were found in 49 patients.